Pentecostalism as a Christian mystical tradition - Castelo, Daniel, 1978- (William B. Eerdmans Publishing Company, 2017)
Pentecostalism, says Daniel Castelo, is commonly framed as "evangelicalism with tongues" or dismissed as simply a revivalist movement. In this book Castelo argues that Pentecostalism is actually best understood as a Christian mystical tradition. Taking a theological approach to Pentecostalism, Castelo looks particularly at the movement's methodology and epistemology as he carefully distinguishes it from American evangelicalism. Castelo displays the continuity between Pentecostalism and ancient church tradition, creating a unified narrative of Pentecostalism and the mystical tradition of Christianity throughout history and today. Finally, he uses a test case to press the question of what the interactions between mystical theology and dogmatics could look like.